Investigation of the wound healing potential of Onosma hispidum root extract in rabbit models - Ali, Asad; Hussain, Fatma; Shahid, Muhammad (Progress in Nutrition, 2015)
Onosma hispidum Wall. (Boraginaceae) has historically been used to treat a wide assortment of diseases. Present study was conducted to investigate the wound healing activity of Onosma hispidum root extracts in animal models. Excision wound were inflicted upon four groups of five rabbits each. Group 1 assigned as vehicle (negative control) was treated with petroleum jelly. Group 2 and 3 were treated with O. hispidum MeOH and n-hexane extracts. Group 4 (positive control) was accorded standard drug polyfax. Healing was assessed by the percentage of wound contraction and histopathological analysis. Animal models treated with n-hexane and MeOH extracts ointments of O. hispidum had significantly (p < 0.05) positive healing effects as compared to the negative controls. Significant reduction (54-56%) in terms of percentage wound contractions were observed in plant treated groups as compared to the vehicle control. O. hispidum treatment resulted in partially developed dermal layer with stratified squmaous, stratum corneum and stratum germinatium development. Although major bioactive principles involved are yet to be determined, this investigation reveals the potential of O. hispidum for use as a natural wound curing agent.